Recurrent Candida-Associated Esophageal Strictures in an Immunocompetent Patient. Issue 5 (19th May 2021) - Narang, Natasha; Pinillos, Hugo; Amog-Jones, Glenda; Gomez, Adam; Alishahi, Yasmin
ABSTRACT: Esophageal stricture due to Candida esophagitis is a rare complication reported among immunocompromised patients in only limited case reports. We describe a unique case of a 36-year-old man with chronic mucocutaneous candidiasis without underlying immunocompromise who experienced over 10 years of recurrent dysphagia due to esophageal strictures from candidiasis. His symptoms were initially believed to be due to eosinophilic esophagitis; however, numerous biopsies from the esophagus were negative for eosinophils. Several upper endoscopies, however, did reveal fungal elements consistent with Candida spp. He experienced recurring episodes of dysphagia and persistent esophageal stricture, requiring multiple antifungal courses and endoscopic balloon dilatations.